The Influence of the Maxillary Posterior Region on Smile Aesthetics in a Chinese Cohort - Ning Wei; Cui Wang; Yanling Zhang; Yiping Wei; Wenjie Hu; Xu Yang; Kwok-Hung Chung (Elsevier, 2022)
Objectives: The aim of this research was to establish standard norms for posterior smile-related characteristics including posterior smile line (PSL), the most posterior teeth displayed, buccal corridor ratio (BCR), and buccal corridor symmetry (BCS) and investigate its aesthetic contributions to smile attractiveness in a Chinese population. Materials and methods: From digitally recorded dynamic smile videos of young Chinese participants, 188 standardised full-smile images were captured and then aesthetically evaluated by 22 laypersons using a visual analog scale (VAS). Four smile-related variables in the posterior region were analysed. VAS data were compared between subgroups to test the influence of these variables on smile aesthetics with significance level of P < .05. Results: The VAS scores of participants with high PSL were significantly lower than those with average or low PSL (P < .01), especially when they display average or low anterior smile line (P < .05). Smiles with the second premolar displayed obtained the highest VAS amongst the 3 subgroups (P < .05). No significant differences were found between the VAS scores of BCR and BCS (P > .05). Conclusions: Maxillary posterior gingiva and teeth displayed influence smile attractiveness evaluated by laypersons, which should be given attention when treating patients with compromised aesthetics, especially those displaying average or low anterior smile lines.